Learning Strategies at TK Aisiyah 2 Boro During Covid-19 Pandemic - Yela Fitrya Sa’diah; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
The purpose of writing this research is to find out how the learning models that exist in schools during the pandemic like today. As well as explaining how the usual learning at TK Aisyiyah 2 Boro was carried out during the Covid-19 pandemic. The research method used is descriptive qualitative research. Namely a study that understands social or human problems by analyzing words to create a complex and comprehensive picture, and reporting views of detailed information obtained from sources in an environment. In this study, it explains what kind of learning models carried out by Kindergarten Aisyiyah 2 Boro, such as when the pandemic level was still high the school was doing full online learning, and after observing that this pandemic had gradually decreased, the school carried out offline learning at school with the consent of parents. Even though offline is only done 3 times a week in turn, the school also provides online learning. With parents taking and collecting teaching materials for students every Friday. Even though when held offline at school, the school also applies health protocols according to the 3M government, namely washing hands, maintaining distance and using masks. Lessons that are usually taught to students are memorizing short letters, daily prayers, memorizing Asmaul Husna, recognizing colors, shapes and also teaching how to read and count. The school also often explains who the founders of Muhammadiyah are, introducing the symbols of Muhammadiyah and Aisyiyah.